Effective separation of protein from Polygonatum cyrtonema crude polysaccharide utilizing ionic liquid tetrabutylammonium bromide - Xu, Yuling; Xu, Jing; Fan, Zheng; Zhang, Siyuan; Wu, Yuanjie; Han, Rongchun; Yu, Nianjun; Tong, Xiaohui (Frontiers in Chemistry, 2024)
Extraction of plant polysaccharides often results in a large amount of proteins, which is hard to eliminate from the crude extract, and conventional approaches for deproteinization are time-consuming and often involve hazardous organic solvents. In this study, ionic liquid tetrabutylammonium bromide (TBABr) was used to create an ionic liquid aqueous two-phase system (ILATPS) for the separation of the polysaccharide (PcP) and protein extracted from the rhizome of Polygonatum cyrtonema. Bovine serum albumin (BSA) was first applied to assess the feasibility of the ILATPS, and MgSO4 was determined to be the most suitable inorganic salt. By adopting the Taguchi experiment with an L9 (3^4) orthogonal array, it was found that the best condition for the efficient separation of crude PcP was at 25°C, with 1.5 g of TBABr, 15 mg of PcP, and 2.0 g of MgSO4, with the extraction efficiency for the protein and polysaccharide as 98.6% and 93.5%, respectively. The purified PcP was homogeneous, and its weight average molecular weight (Mw) was 7,554 Da. Monosaccharide composition analysis indicated the PcP comprised mannose, galactose, glucose, galacturonic acid, arabinose, and rhamnose at a molar ratio of 33:13:8:3.5:2:1. This approach offers a practical tactic to purify polysaccharides of plant origin.